Presidential leadership and strategic planning: a case study - Hough, Annette D. (Kansas State University, 2021)
This study explored how a community college president used strategic planning concepts to advance an institution’s completion agenda initiatives. The research method was a qualitative single case study design. Keller’s (1983) academic strategy served as the conceptual framework to conduct the investigation. Four research questions guided the investigation: 1) How did the participants describe the strategic planning process at the college? 2) How did the participants describe the president's strategies in facilitating the strategic planning process? 3) How did the participants describe the reasons, internal or external, that contributed to the launch of the institution's completion initiatives? 4) To what extent did the participants describe the strategic planning process to reflect Keller's (1983) academic strategy components? The study sought to identify institutional strategies and practices used to advance the completion agenda within the selected community college. Participants shared ways the college president communicated and incorporated stakeholders in the planning efforts. Eight significant emerging themes emerged from the analysis of data: values, leadership, external factors, internal factors, data, student focus, board of trustees, and competitive situation. According to the participants in the study, all eight of these factors contributed to the strategic planning strategies of the community college president’s planning process. The results of the study revealed evidence of a participatory strategic planning effort where all stakeholders within the organization were engaged in the strategic planning process. The findings also suggested that the president’s strategic planning approach engaged a comprehensive communication strategy with student-first priorities to establish institutional goals.
Keywords: Strategic planning; Completion agenda; Communications; Strategy planning processAcademic strategy